TINJAUAN TRAINING HUMAN FACTOR PADA DEPARTEMEN PENDIDIKAN DAN PELATIHAN PT. DIRGANTARA INDONESIA - Meddy Nurpratama; Agus Yudianto (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2021)
The aim of the training center is to become part of the human resource development program through the initiation and execution of trainings for all employees which include the implementation of new employee orientation, fulfillment of JDQ Requirements, technology development, management development, compliance with regulations and customer requirements. Carrying out the assessment test function for prospective officials at the supervisor and manager level, Talent Management and coordinating the implementation of Pre-retirement Training for all employees.The materials in the Human Factor training are human factor overview, human error & violation, human abilities & limitations, memory & perception, management of stress & fatigue, communiaction, situational awareness, decision making, teamwork, error prevention.